The only guide you'll ever need for the right financial plan : managing your wealth, risk, and investments - Swedroe, Larry E.; Grogan, Kevin; Lim, Tiya (Bloomberg Press, 2010)
"A guide that outlines the key elements of an effective financial plan.From Larry Swedroe, the author of the bestselling series of "The Only Guide" investment books, with Kevin Grogan and Tiya Lim comes a step-by-step handbook that shows you how to develop a winning personal investment strategy and reveals what it takes to make that strategy part of your overall financial plan. The Only Guide You'll Ever Need for the Right Financial Plan focuses on the "art" of investing and gives you the information you need to create a strategy that is tailor-made for your particular situation. Designed for savvy investors and professional advisors, this book offers the vital information needed for developing and implementing an overall strategic financial plan. In this resource, Swedroe outlines the basics in asset allocation and other investment planning concepts. Addresses how you can design an investment policy statement and an individual asset allocation plan. Examines how to maintain your portfolio's risk profile in the most cost-effective and tax-efficient manner. Offers insights on integrating risk management and estate planning issues into your plan.The Only Guide You'll Ever Need for the Right Financial Plan offers a handy tool to help you make more informed and prudent decisions that will go a long way to ensure a secure financial future..."--Jacket